(untitled) (ALUSTATH JOURNAL FOR HUMAN AND SOCIAL SCIENCES, 2018)
For many years, time travel was the stuff of science fiction. This was all just part of the world’s imagination until recently. Science authors, among them, Kurt Vonnegut (1922-2007) post-modern American writer, believe that one can travel through time forward or backward asking his memories and stream of consciousness to give sensory impressions of his thoughts and actions, that what Billy did in Vonnegut’s Slaughter house- Five (1969). The protagonist Billy Pilgrim finds himself "unstuck in time" jumping between several periods of his life. Travelling between his experiences as a prisoner of war in World War II to his family life in 1950s, and 1960s and his time on Tralfmadorian Planet, Billy has the freedom and ability to travel; he has no control over these transitions. The present study falls into three sections plus a conclusion. The first section deals with the concept of time travel in literature and fiction. Section two presents historical and literary context to Vonnegut’s novel. The treatment of time travel concept will be discussed in the third section. Then, the conclusions which sum up the findings of the research.